Science and the Green Revolution in the Brazilian Amazon: The Establishment of Embrapa during of the Civilian-Military Dictatorship and the Emergence of Environmental Movements (1972-1991) - Silva e Mello, Vanessa Pereira da; Sá, Dominichi Miranda de (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2022)
The Empresa Brasileira de Pesquisa Agropecuária (Brazilian Agricultural Research Corporation), known by the acronym Embrapa, was established in 1972 under Brazil’s civilian-military dictatorship with the purpose of fostering agricultural modernization through the incorporation of the Green Revolution’s technology package, which included reliance on chemical inputs and high-yielding hybrid seeds and the mechanization of production. This article explores the context in which the agency was established and its scientific research agenda for Brazilian agriculture, while also examining both the influence of emerging environmentalist movements on discussions of the economic exploitation of the Amazon as well as the agency’s profile during the period of redemocratization in Brazil. The focus of our analysis is on the agency branch known as the Humid Tropics Agricultural Research Center (Centro de Pesquisa Agropecuária do Trópico Úmido, or CPATU), which opened in Belém, Pará, in 1975. The text follows the path of the CPATU through 1991, when it became the Eastern Amazon Agroforestry Research Center (Centro de Pesquisa Agroflorestal da Amazônia Oriental), now Embrapa Eastern Amazon (Embrapa Amazônia Oriental).